Domain wall dynamics of periodic magnetic domain patterns in Co2MnGe-Heusler microstripes - K Gross; K Westerholt; H Zabel (New Journal of Physics, 2016)
Highly symmetric periodic domain patterns were obtained in Co _2 MnGe-Heusler microstripes as a result of the competition between growth-induced in-plane magnetic anisotropy and shape anisotropy. Zero field magnetic configurations and magnetic field-induced domain wall (DW) motion were studied by magnetic force microscopy-image technique for two different cases: dominant uniaxial - and dominant cubic in-plane anisotropy. We implemented a magneto-optical Kerr effect susceptometer to investigate the DW dynamics of periodic domain structures by measuring the in-phase and out-of-phase components of the Kerr signal as a function of magnetic field frequency and amplitude. The DW dynamics for fields applied transversally to the long stripe axis was found to be dominated by viscous slide motion. We used the inherent symmetry/periodicity properties of the magnetic domain structure to fit the experimental results with a theoretical model allowing to extract the DW mobility for the case of transverse DWs ( μ _TDW  = 1.1 m s ^−1 Oe ^−1 ) as well as for vortex-like DWs ( μ _VDW  = 8.7 m s ^−1 Oe ^−1 ). Internal spin structure transformations may cause a reduction of DW mobility in TDWs as observed by OMMFF simulations.